PENGARUH KETIDAKSEIMBANGAN BEBAN TERHADAP STABILITAS STEADY STATE - Asmar Asmar (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2018)
The stability of the electric power system is related to the balance of power in the system. When a power change occurs, the rotor will swing affecting the power angle, rotation speed, frequency and stability of the system. The Unbalanced load causes the momentary power of the generator to contain the sinusiodal component. To know the effect of sinusiodal component, must be known relation between power angle with momentary power. The relationship is determined by the symmetric component method. The power angle relationship with the momentary power obtained is applied to the swing equation. With the linearization of the equation, it can be seen the effect on steady state generator stability. The results showed that an increase in load imbalance caused a decrease in the stability limit.